Perbandingan Tingkat Kebahagiaan Petani Tembakau dan Peternak Sapi Perah di Kabupaten Tulungagung - Proborini, Nur Alvina; Ibrahim, Jabal Tarik; Ariadi, Bambang Yudi (Universitas Galuh, 2025)
The agricultural sector plays an important role in the economic aspect to achieve national development. The agricultural sector includes the tobacco commodity plantation sub-sector and dairy cattle farming. The decent living conditions in the community can be seen in the economic and social aspects. The social aspect of human resource development is a special concern to describe true welfare. The welfare of farmers and livestock breeders needs to be considered as the main actors in the agricultural sector. Human welfare is measured by two indicators objectively and subjectively. Subjective welfare or happiness consists of personal and social life satisfaction, meaning of life, and meaning of life. The study aims to present an empirical analysis of the level of happiness of tobacco farmers and dairy farmers in Tulungagung Regency. The research respondents were determined by purposive sampling, namely 50 tobacco farmers and 50 dairy farmers. The results of the study showed that the happiness index of tobacco farmers was 7.77 in the happy category while dairy farmers were 8.27 in the very happy category.